Functional State of Respiratory Muscles in Patients with Chronic Obstructive Pulmonary Disease - I. G. Kurpаtov; B. I. Geltser; V. N. Kotelnikov; M. F. Kinyaykin (Туберкулез и болезни лёгких, 2021)
The objective: to assess the strength of respiratory muscles (RM) in patients with chronic obstructive pulmonary disease (COPD) and determine the role of certain pathogenetic factors of COPD in the development of respiratory muscle dysfunction.Subjects and methods. In in-patient settings, the strength characteristics of respiratory muscles were studied in 85 men aged 39-78 years suffering fromCOPD exacerbation. MicroRPM (CareFusion, UK) was used to determine the levels of maximum inspiratory and expiratory pressures in the oral cavity, maximum rate of their rise during inspiration and expiration as well as the level of intranasal pressure before and after the test with salbutamol.Results. Significant variability in strength characteristics of respiratory muscles was observed depending on the stage of COPD, its phenotype, and the presence of hypoxemia or hypercapnia. In patients at early stage of COPD, only expiratory respiratory muscle dysfunction was documented; at moderate and severe stages, inspiratory and expiratory muscle dysfunction was observed, and at very severe stage – diaphragm dysfunction prevailed. The results of the salbutamol test demonstrated the maximum increase in the strength of respiratory in early and moderate COPD and the minimum increase in extremely severeCOPD indicating the role of the irreversible component of bronchial obstruction in the development of respiratory muscle dysfunction. The emphysematous phenotype of COPD was characterized by inspiratory respiratory muscle dysfunction, while the bronchitic phenotype was characterized by expiratory respiratory muscle dysfunction. In patients with hypoxemia and hypercapnia, the strength of inspiratory respiratory muscle was lower versus normoxemia.